Derivative Spectrophotometric Determination of Trace Manganese after Separation and Preconcentration with the Ion Pair of 2-(5-Bromo-2-pyridylazo)-5-diethylaminophenol and Ammonium Tetraphenylborate - Ali Taher, Mohammad (Asian Journal of Chemistry, 2010)
Manganese is quantitatively retained on 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (5-Br-PADAP)-ammonium tetraphenylborate with microcrystalline naphthalene or by a column method in the pH range 7.5–10.5 from a large volume of aqueous solutions of various samples. After filtration, the solid mass consisting of the manganese complex and naphthalene was dissolved with 5 mL of dimethylformamide and the metal was determined by third derivative spectrophotometry. Manganese complex can alternatively be quantitatively adsorbed on ammonium tetraphenylborate- naphthalene adsorbent packed in a column and determined similarly. About 0.1 μg of manganese can be concentrated in a column from 500 mL of aqueous sample, where its concentration is as low as 0.2 ng/mL. The interference of a large number of anions and cations has been studied and the optimized conditions developed were utilized for the trace determination of manganese in various samples.